Does a Satisfied Student Make a Satisfied Worker? - Adele Whelan; Seamus McGuinness (Institute of Labor Economics (IZA), 2017)
We investigate the effect of satisfaction at higher education on job satisfaction using propensity score matching, the special regressor method and a unique European dataset for graduates. Acknowledging that perceptions of satisfaction at higher education are endogenous to job satisfaction, we present models available to the deal with this endogeneity. Our analysis confirms that a positive university experience is important for success in future employment and suggests that emphasis should be focused on the utility of participating in third-level education along with academic outcomes.
Keywords: J20; J28; I23; I31; 330; graduate labour market; job satisfaction; higher education